Android"!for Programmers : an App-Driven Approach - Deitel, Paul; Deitel, Harvey; Deitel, Abbey; Morgano, Michael (Prentice Hall, 2011)
The professional programmer's Deitel® guide to Android"!smartphone and tablet app development and the Eclipse IDE with the Android Development Tools (ADT) plug-in ¿ Billions of apps have been downloaded from Android Market! This book gives you everything you'll need to start developing great Android apps quickly and getting them published on Android Market. The book uses an app-driven approach-each new technology is discussed in the context of 16 fully tested Android apps, complete with syntax coloring, code walkthroughs and sample outputs. Apps you'll develop include: SpotOn Game Slideshow Flag Quiz Route Tracker Favorite Twitter® Searches Address Book Tip Calculator Doodlz Weather Viewer Cannon Game Voice Recorder Pizza Ordering Practical, example-rich coverage of: Smartphone and Tablet Apps, Android Development Tools (ADT) Plug-In for Eclipse Activities, Intents, Content Providers GUI Components, Menus, Toasts, Resource Files, Touch and Gesture Processing Tablet Apps, ActionBar and AppWidgets Tweened Animations, Property Animations Camera, Audio, Video, Graphics, OpenGL ES Gallery and Media Library Access SharedPreferences, Serialization, SQLite Handlers and Multithreading, Games Google Maps, GPS, Location Services, Sensors Internet-Enabled Apps, Web Services, Telephony, Bluetooth® Speech Synthesis and Recognition Android Market, Pricing, Monetization And more ... PLUS: Register your product at www.informit.com/register for additional online chapters that cover Android Ice Cream Sandwich (Android 4), including a complete, working Ice Cream Sandwich app! ¿ VISIT WWW.DEITEL.COM For information on Deitel's Dive Into® Series instructor-led programming language training courses offered at customer sites worldwide visit www.deitel.com/training or write to deitel@deitel.com Download code examples Check out the growing list of programming Resource Centers Join the Deitel Twitter (@deitel) and Facebook (www.facebook.com/DeitelFan) communities To receive updates for this book, subscribe to the free Deitel ® Buzz Online e-mail newsletter at www.deitel.com/newsletter/subscribe.html.